Discovery of the ROCK inhibitor netarsudil for the treatment of open-angle glaucoma. Issue 10 (15th May 2016) - Sturdivant, Jill M.; Royalty, Susan M.; Lin, Cheng-Wen; Moore, Lori A.; Yingling, Jeffrey D.; Laethem, Carmen L.; Sherman, Bryan; Heintzelman, Geoffrey R.; Kopczynski, Casey C.; deLong, Mitchell A.
Graphical abstract: Abstract: Inhibition of Rho kinase (ROCK) to improve fluid outflow through the trabecular meshwork and lower intraocular pressure is a strategy for the development of new anti-glaucoma agents. Alpha-aryl-beta-amino isoquinoline analogs were identified as potent ROCK inhibitors. Compounds that provided a longer duration of intraocular pressure reduction in Dutch Belted rabbits also inhibited norepinephrine transporter. Ester60 improved bioavailability of its parent ROCK inhibitor, 29 ( K i = 0.2 nM) and demonstrated an effective and sustained IOP reduction for 24 h after dosing. From these studies, netarsudil (a.k.a. AR-13324) was discovered and is currently in clinical trials for the treatment of glaucoma and ocular hypertension.